Iustitia, Concordia, Pax Vermittlung, Repräsentation und Legitimation von Frieden in Dichtungen zwischen 1648 und 1763 - Bauer, Franziska (Universitätsverlag Göttingen, 2023)
The early modern period applies to be the age of wars and military conflicts. But every military attack or combat action was followed of a truce or a peace treaty. But how were those changes in state conveyed into society and which reactions were aroused? This thesis concentrates on occasional poetry as a part of the early modern media to convey the message of peace, the representation of peace and respective strategies of legitimacy of a certain peace treaty and therefore, identifies early modern ideas and concepts of peace. The focus is on selected peace treaties between 1648 and 1763. The comparative method allows to draw conclusions on historical continuity and historical changes.